Locating a complex inhomogeneous medium with an approximate factorization method. (5th March 2019) - Qu, Fenglong; Zhang, Haiwen
Abstract: Consider the inverse problem of scattering of time-harmonic acoustic waves by an inhomogeneous medium with complex refractive index. We show that an approximate factorization method can be applied to reconstruct the support of the complex inhomogeneous medium from the far-field data. Numerical examples are also provided to illustrate the practicability of the inversion algorithm.